Catalytic hydrogenation of alkali lignin into bio-oil using flower-like hierarchical MoS2-based composite catalysts. (1st December 2016) - Li, Naixu; Wei, Lingfei; bibi, Rehana; Chen, Lingyu; Liu, Jiahui; Zhang, Li; Zheng, Yiqun; Zhou, Jiancheng
Highlights: MoS2 and MSx /MoS2 (M = Ni, Co, Ag) were prepared via the hydrothermal method. Catalysis of MoS2 at various reaction conditions was examined. A surprising conversion of lignin and yield of bio-oil was obtained with CoS2 /MoS2 . Cooperation of different metallic sulfide could enhance the catalytic performance. Abstract: Given the low price and abundance of alkali lignin from pulp and paper industry, the conversion of alkali lignin into valuable chemicals has been of great significance to address the world energy crisis. In principle, this process has long relied on the design of a functionalized catalyst to enable high reactivity and selectivity. Herein, we present a systematic study on the hydrogenation liquefaction of alkali lignin using a series of flower-like hierarchical MoS2 –based catalysts, in which, the effect of various reaction parameters, such as temperature, H2 pressure, and reaction time, on product yield and distribution was evaluated. Catalysts were characterized by Powder X-ray diffraction, transmission electron microscopy and scanning electron microscopy. N2 adsorption-desorption isotherms, surface area, pore size distributions and the average pore diameter of catalysts were also measured and calculated. It is worth noting that the incorporation of a secondary metal sulfide into MoS2 could significantly enhance the catalytic performance. Particularly, by using 5 wt% CoS2 /MoS2 as catalyst and having H2 pressure, reaction temperature, and reaction time set to be 2.5 MPa, 310 °C, and 1 h, respectively, the highest conversion of alkali lignin could reach 91.26%, with a bio-oil yield of 86.24%. This work thus offers an effective approach to improve the conversion and selectivity in catalytic hydrogenation of alkali lignin into bio-oil by using MoS2 –based catalysts.